Fabrication of novel AgBr/Bi24O31Br10 composites with excellent photocatalytic performance. Issue 68 (23rd November 2018) - He, Zuming; Xia, Yongmei; Su, Jiangbin
Abstract : XRD patterns of pure AgBr, Bi24 O31 Br10 and AgBr/Bi24 O31 Br10 nanocomposites. Abstract : Novel porous AgBr/Bi24 O31 Br10 (AB/BOB) heterojunction composites were prepared by a hydrothermal calcination-ion exchange route and their physico-chemical properties were characterized by XRD, XPS, SEM, EDX, UV-vis DRS, BET and electrochemical measurements. The photocatalytic activity of the composites consisting of different AB/BOB mass ratios was evaluated by degradation of methylene blue (MB) under visible light irradiation. Compared with pure AB and BOB, the porous 20% AB/BOB composite exhibits much enhanced photocatalytic activity with good cycling stability. The significant enhancement in photoactivity is contributed to by both a high adsorption capacity and the separation efficiency of photo-generated electron–hole (e − –h + ) pairs via a Z -scheme mechanism. In addition, radical scavenging experiments confirm that the reactive ·OH radicals play an important role in the photocatalytic reaction. The novel (AB/BOB) heterojunction composites could have a promising application in treatment of various dyestuff wastewaters on a large scale.